Monitoring and Diagnostics of SOFC Stacks and Systems. (10th July 2019) - Mougin, Julie; Morel, Bertrand; Ploner, Alexandra; Caliandro, Priscilla; Van Herle, Jan; Boškoski, Pavle; Dolenc, Boštjan; Gallo, Marco; Polverino, Pierpaolo; Pohjoranta, Antti; Nieminen, Aki; Pofahl, Stefan; et al.
Abstract : While high performance of SOFC systems has already been achieved, there is still a need to increase the stack lifetime, while decreasing the system's total cost of ownership, both being linked. The increase in lifetime includes the minimization of performance degradation, but also avoidance of potentially detrimental events during operation, originating from the stack, outside the stack, or a combination of both. The present paper highlights how the detection of faulty operation as early as possible is important to implement adequate mitigation strategies, wherever applicable, according to the fault and its grade of severity. Three types of faults have been considered, fuel starvation, leakage and carbon deposition. Both hardware components and algorithms to monitor, detect, isolate, and finally correct faulty system operation have been developed and will be embedded in a real SOFC system.